Chlorophyll a Fluorescence as a Tool in Evaluating the Effects of ABA Content and Ethylene Inhibitors on Quality of Flowering Potted Bougainvillea - Antonio Ferrante; Alice Trivellini; Eva Borghesi; Paolo Vernieri (The Scientific World Journal)
Flowering potted plants during the postproduction stage are usually stored in inadequate environmental conditions. We evaluated the effect of the most common storage conditions and treatments on two Bougainvillea cultivars after harvest and during recovery. Flowering potted Bougainvillea plants were treated with 100 mL 2 mM amino-oxyacetic acid (AOA) or 500 ppb 1-methylcyclopropene (1-MCP) prior storage in dark at 14∘C for simulating transport or storage conditions and, subsequently, transferred to growth chambers at 20∘C in the light for one week for evaluating the recovery ability. The plant stress during the experiments was assessed by ethylene, ABA, and chlorophyll a fluorescence measurements. Ethylene production was affected by temperature rather than treatments. ABA concentration declined in leaves and flowers during storage and was not affected by treatments. Fluorescence parameters appear to be very useful for screening Bougainvillea cultivars resistant to prolonged storage periods.